Efforts to Increase The Effectiveness of Learning Disc Throwing With Plastic Plate Modified Media in Class VII.4 of SMP Negeri 9 Kendari - Mansur (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2023)
This study aims to improve the effectiveness of discus throwing learning outcomes using modified plastic plates in class VII SMP Negeri 9 Kendari. The subjects studied were students of class VII.4, totaling 36 students, with details of 18 male students and 18 female students. The implementation consists of 2 cycles. Each studied cycle is adjusted to the design changes in the investigated factors. The procedure of this research: (1) planning, (2) implementation of the action, (3) observation, and (4) reflection. Data sources are students and teachers. The data obtained is qualitative data through observation sheets and journals and quantitative data through learning achievement tests. The results showed that (1) student activity using a modified plastic plate media was considered active while participating in the discus throwing learning process. And after the second cycle was carried out, student activities experienced an average increase in activity by 80.5%; (2) the teacher's teaching activities in the first cycle reached an achievement level of 90%, while in the second cycle, after conducting treatment in the learning process, the teacher's activity reached 96%. This means that there is an increase in teacher activity by 6%, so that the average teacher activity in the two cycles reaches 93%; (3) the average learning completeness for the prefix aspect reaches 93.05% for boys and 76.35% for girls; (4) the average learning completeness for the Throwing Method aspect reached 84.35% for boys, and 72.2% for girls; (5) the average Learning Completeness aspect for the aspect of Final Attitude reaches 82.65% for boys and girls reaches 73.65%, and (6) student responses refer to Student Response Indicators, so the average student response rate is 84%, has the criteria Very Satisfied